Applying 3d Printing Technologies On Recontextualizing The Rebab Melayu As A Contemporary Musical Instrument - Hanif, Mhd Sany Mhd (2024)
This doctoral thesis delves into the transformative exploration of redefining the Rebab Melayu, an iconic Malaysian musical instrument, by harnessing the innovative potential of 3D printing technology within the domain of product design. Amid its prevalent use in Makyong and Main Puteri performances, the Rebab Melayu confronts diminishing relevance in contemporary times due to challenges posed by modernization and scarcity of traditional materials, triggering environmental constraints. This study critically examines the viability and implications of employing 3D printing technology to replicate and potentially revitalize the Rebab Melayu, comprehensively evaluating its challenges, merits, and feasibility. The research methodology employs a multifaceted approach encompassing the identification of traditional Rebab Melayu characteristics, the implementation of 3D printing technology for crafting a contemporary instrument, empirical testing through video documentation of the manufacturing process and instrument performance, and a thorough analysis of audience responses during a contemporary music performance.